2013
DOI: 10.1080/0371750x.2013.867644
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, Photocatalytic Activity and Conductivity Studies of YLnTi2O7(Ln = Nd, Sm, Eu and Gd)

Abstract: IntroductionTernary oxides with general formula A 2 B 2 O 7 or A 2 B 2 O 6 O are isostructural to the mineral pyrochlore, (NaCa)(NbTa)O 6 F/OH. 1 Eight coordinate A site can be occupied by trivalent lanthanides, divalent alkaline earth or monovalent alkali ions. Site B can be filled by six coordinate tetravalent (Ti 4+ , Zr 4+ , Hf 4+ and Sn 4+ ) or pentavalent (Nb 5+ and Ta 5+ ) ions for charge neutrality. These materials have received considerable attention for their remarkable properties and potential appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated the favorable photocatalytic capability of A 2 B 2 O 7 and AB 2 O 6 mixtures under visible light exposure (VLE) [33][34][35][36][37][38][39]. For instance, Devi et al achieved a photocatalytic removal efficiency (REF) of 66% for methylene blue (0.1 mmol/L) using the photocatalyst YGdTi 2 O 7 under VLE for 180 min [40]. Similarly, Zhang et al reported an REF of 69.7% for methyl orange (20 mg/L) using the photocatalyst Gd 2 Ce 2 O 7 powder under VLE for 300 min [41].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the favorable photocatalytic capability of A 2 B 2 O 7 and AB 2 O 6 mixtures under visible light exposure (VLE) [33][34][35][36][37][38][39]. For instance, Devi et al achieved a photocatalytic removal efficiency (REF) of 66% for methylene blue (0.1 mmol/L) using the photocatalyst YGdTi 2 O 7 under VLE for 180 min [40]. Similarly, Zhang et al reported an REF of 69.7% for methyl orange (20 mg/L) using the photocatalyst Gd 2 Ce 2 O 7 powder under VLE for 300 min [41].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated the excellent photocatalytic performance of AB 2 O 6 and A 2 B 2 O 7 compounds under visible light exposure [38][39][40]. For instance, Devi et al demonstrated that under visible light exposure for 180 min, the YGdTi 2 O 7 nanophase material achieved a photocatalytic removal efficiency (RME) of 66% for methylene blue [41]. Similarly, Zhang et al studied that the La 2 Ce 2 O 7 photocatalyst powder achieved an RME of 76.6% for methyl orange under visible light exposure for 300 min [42].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies are concerned with metal oxide photocatalysts (with the chemical formula A 2 B 2 O 7 crystallized in a pyrochlore structure) for dye photodegradation. Some examples include Ln 2 Ce 2 O 7 (Ln = Nd, Pr, or Eu) for the degradation of methylene blue (MB) dye [29], YLnTi 2 O 7 (Ln = Nd, Sm, Eu, or Gd) for the degradation of MB [30], K 2 Ta 2 O 6 for the degradation of rhodamine B [31], and Y 2 Ti 2 O 7−x N x for the degradation of MB, rhodamine B, and 4-chlorophenol [32]. Less attention is given to metal oxides with the chemical formula A 2 B 2 O 7 in the defect fluorite phase.…”
Section: Introductionmentioning
confidence: 99%